Brucellosis in a patient diagnosed with Coronavirus Disease 2019 (COVID-19) - Mehmet Güven (Journal of Infection in Developing Countries)
Brucellosis is a common zoonotic infection. Brucellosis typically presents with fever, weakness, night sweats, and arthralgias. Symptoms associated with Coronavirus Disease 2019 (COVID-19) and infection with Brucella spp. are similar to one another, which may lead to delayed diagnosis of the latter condition. There are no previous reports of brucellosis in a patient previously diagnosed with COVID-19. We present here the case of a 20-year-old male who we diagnosed with brucellosis after joint pains and fever that persisted after resolution of COVID-19.